Assimilation in multilingual cities - Javier Ortega; Gregory Verdugo (Institute for the Study of Labor (IZA), 2011)
Using the Public Use Microdata Files of the 2001 and 2006 Canadian Censuses, we study the determinants of the assimilation of language minorities into the city majority language. We show that official minority members (i.e. francophones in English-speaking cities and anglophones in French-speaking cities) assimilate less than the allophones (the individuals with a mother tongue other than English or French), and that immigrants generally assimilate less than natives. In addition, the language composition of cities is shown to be an important determinant of assimilation both for allophones and for official minorities. Finally, we show that assimilation into French in French-majority cities is lower than assimilation into English in English-majority cities even when controlling for the language composition of the cities and including a rich set of language dummies.
urn:nbn:de:101:1-201203014795
Keywords: F22; J15; 330; immigration; assimilation; language policies; minorities; Migranten; Mehrsprachigkeit; Soziale Integration; Kanada